EFFECTS OF REGULATORY AUTHORITIES ON SUGAR MARKETS: AN EVALUATION ON THE USA CASE - Nar, Mehmet; Nar, Mehmet Şükrü (International Journal of Contemporary Economics and Administrative Sciences, 2020)
Studies have shown that public regulatory authorities can serve self-interest instead of public interest. The US sugar market can be given as a concrete example of this situation. Regulatory actions for the sugar market have led to the widespread use of high fructose corn syrup, which has been called the plague of the age. The production of high fructose corn syrup, which has increased day by day in the US, has reduced sugar imports and significantly contributed to the economy with its undisputed role in the food sector. However, at the same time, the increase in chronic diseases and chronic health expenditures in the US has come to the fore as a problem that needs to be addressed. This study primarily focused on the activities of regulatory bodies and then emphasized the existence of the causality relation between the increase in high fructose corn syrup production and consumption, and the increase in health costs. The findings of this study supported the negative perceptions and judgments the society has towards high fructose corn syrup. In addition, the study was conducted within the framework of the 3rd best policy, which has been rarely used in the literature, and presents how public efficiency can be achieved.